A novel design of a damping failure free energy-harvesting shock absorber system. (1st October 2019) - Li, Shiying; Xu, Jun; Pu, Xiaohui; Tao, Tao; Mei, Xuesong
Highlights: A novel design of energy-harvesting shock absorber control system is proposed. Damping fluctuation and damping failure zone can be eliminated with the system. The system can regulate the damping coefficient in real-time and harvest energy. The system is characterized with high energy recovery efficiency of 58.19%−70.55%. A high response speed of 4 Hz that can meet the application requirement is obtained. Abstract: An energy-harvesting shock absorber can adjust the damping coefficient in real time to meet the vibration reduction, and it can also harvest energy from the vibration of a suspension. This paper proposed a novel design for an energy-harvesting shock absorber system. The study focusses mainly on the realization of energy harvest and damping control. A closed loop damping control strategy is proposed, with which, the shock absorber is not only able to supply a controllable electromagnetic damping force but can also harvest energy from the vibration. The system construction and working principle is introduced, and the experiment platforms are established. A series of simulations and experiments were conducted to demonstrate the effectiveness of the proposed shock absorber system. The results show that an average energy recovery efficiency of 40.72%–70.55% can be obtained when tested under sinusoidal excitation and random road excitation. The proposed system is characterized by a high response speed of 4 Hz, and it can meet the operating requirements under random road excitation. The results also indicate that the damping coefficient can be adjusted with a high precision of 93.56%, and thus, both the damping failure and damping fluctuation are effectively eliminated.